DIAGNOSING THE TYPE OF DYNAMICS OF SOCIO-ECONOMIC SYSTEMS USING TOPOLOGICAL TESTS (THE EU IS TAKEN AS AN EXAMPLE) - M. Golovanenko (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The possibility of practical realization of the simplest elements of topological tests that are used to identify the type of systems’ dynamics is considered in the article. The tests were fulfilled by the means of standard instruments of Microsoft Excel. The analysis of time series of industrial production indices of EU 17 countries as a whole and individual countries, such as Germany, France, Great Britain and Greece has shown that these series are characterized by existence of attractors. This can be interpreted as a sign of existence of deterministic chaos and evidence of the systems’ ability for self-organization and self-regulation. However, a separate area is identified for Greece, where the dynamics of the time series transforms into a random. The area can be interpreted as a sign of “overheating” economy of Greece, which took place before the global crisis and thus deprived the economy of adaptive properties.